Utilization of Social Media in the Dissemination of Arabic Language Knowledge: A Case Study of Instagram Account @taalum.id - Rifki Pratama, Muhammad; Asti Fauziah; Dedy Irawan; Adam Malik (Tarling : Journal of Language Education, 2026)
This study aims to describe the utilization of social media, particularly Instagram,in disseminating Arabic language knowledge through the @taallum.id account,as well as to analyze the content strategies employed to attract followers’ interestand enhance their understanding of the Arabic language. The study adoptsa qualitative approach with a case study design. Data were collected throughobservation, audience engagement analysis, interviews using purposive samplingtechniques, and documentation of four main content categories representingkey aspects of Arabic language learning, namely mufrodat (vocabulary), nahwu(grammar), reading skills, and daily expressions. Data analysis was carriedout through the processes of reduction, presentation, and conclusion drawing.The findings reveal that Instagram is utilized as a medium for disseminatingArabic language knowledge through the use of short educational videos withengaging visuals, accompanied by Arabic text and its translation. The mainstrategies employed by the @taallum.id account include the use of thematichashtags, interactive captions, and calls to action that motivate the audience to participate actively. The interviews with participants confirmed that the content was regarded as educational, engaging, and motivating for learning, particularly through a visual and contextual approach. Thus, the account serves as an effectivealternative medium that supports the digital dissemination and learning of theArabic language while demonstrating the integration between language literacyand media literacy in the information technology era